Naturalism and the Problem of Normativity: The Case of Historiography. Issue 5 (September 2019) - Kuukkanen, Jouni-Matti
This article tackles the problem of normativity in naturalism and considers it in the context of the philosophy of historiography. I argue that strong naturalism is inconsistent with genuine normativity. The strong naturalist faces a difficult dilemma. If he rejects any reliance on conceptual intuitions, his epistemic inquiries will not get off the ground. As a consequence, his analyses of historiography are, in effect, normatively irrelevant: any practice is epistemically as valuable as any other. Another option for the strong naturalist is to relax methodological requirements and accept that epistemic inquiries may begin with nonempirical conceptual reflection or a priori reasoning.